Effects of Irrigation Water Quality on the Recovery of 15N-Fertilizer by Sorghum in Field Study - Khelil, Mohamed Naceur; Destain , Jean Pierre; Rejeb , Saloua; Henchi, Belgacem (Asian Journal of Agriculture and Rural Development, 2011)
15N-labeled fertilizer was applied to Sorghum at different rates (0, 100 kg N.ha-1) to 1m² microplots and with two kind of water (well water “WW” and treated wastewater “TWW”) to Sorghum grown in field during 1997 and 1999. Increases in DM production, N uptake and 15NRF were observed with TWW. About 17% and 36% of the 15N-fertilizer were recovered in the crop with TWW in 1997 and 1999, respectively. Residual effect was higher in TWW (3% vs 5%). Water irrigation quality had no effect on the 15N-labeled fertilizer remaining in the 0-60 cm layer at final harvest. For both water qualities, the major fraction of the residual 15N-fertilizer (about 60%) was recorded in the surface layer. Losses of 15N-labaled fertilizer was unaffected by water irrigation quality being approximately 35% of the applied 15N-fertilizer. TWW irrigation can efficiently substitute WW for irrigation of Sorghum and, simultaneously save nitrogen fertilizer.